Canine Prostatic Disorders: A Comprehensive Pathophysiology and Clinical Management - Singh, Pratyastha; Acharya, Aditya Prasad; Sahoo, Anjan Kumar; Mishra, Chinmoy; Mohapatra, Arpita; Panda, Susen Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
In small animal practice, diseases that affect the canine prostate gland are very common. Benign prostatic hyperplasia, prostatitis, prostatic cysts, and prostatic neoplasia are the most prevalent disorders affecting the canine prostate. Clinical indications linked with each of these illnesses often coincide. Consequently, it is necessary to establish a firm diagnosis prior to treatment. The most reliable and efficient method for diagnosing prostatic conditions in dogs is through ultrasonography. Ten dogs (2.82%) with prostatic illnesses were found out of 355 male dogs that were screened at the Veterinary Clinical Complex, OUAT, Bhubaneswar. Common clinical symptoms recorded were tenesmus, dysuria, and haematuria in dogs that were between the ages of 5 and 13 years. Radiography, ultrasonography, cytology, microbiological analysis, urinalysis, and haemato-biochemical analysis were performed to confirm the disease to be of prostatic origin. Survey abdominal (lateral and VD) radiography and pneumocystography showed prostate size >50% of pelvic inlet and around 90% in prostatic abscess and tumors. In B-mode abdominal ultrasonography images, anechoic, hypoechoic and homogenous area of echoes were visualized in cases of prostatic cyst, prostatic abscess, and benign prostatic hyperplasia respectively. Urine culture from affected animals in nutrient agar showed growth of E. coli colony and was responsive to Nitrofurantoin antibiotic disc. This study emphasizes the effectiveness of castration in treating canine prostatic illnesses as well as the use of ultrasonography in identifying disorders of the prostate gland providing an appropriate strategy for future treatment.
Keywords: B-mode ultrasonography; Fine needle aspiration cytology; Prostate; Prostatic hyperplasia; Radiography